(untitled) (Journal of Artificial Intelligence & Research, 2021)
Evolutionary Design Optimization (EDO) has emerged as a promising paradigm for addressing complex engineering challenges by harnessing the power of generative algorithms. This paper explores the potential of generative algorithms in facilitating EDO processes, focusing on their ability to efficiently explore solution spaces, adapt to changing constraints, and generate novel designs. Through a comprehensive review of existing literature and case studies, we delve into the mechanisms behind evolutionary algorithms and their application in various engineering domains. Key findings highlight the versatility of generative algorithms in optimizing diverse design objectives, from structural robustness to energy efficiency. Moreover, we discuss the integration of machine learning techniques to enhance the performance of EDO methods and overcome computational limitations. This paper aims to provide insights into the evolving landscape of EDO, paving the way for future research directions and practical applications in engineering design.